Brain structural correlates of obsessive–compulsive disorder with and without preceding stressful life events. (3rd July 2016) - Real, E.; Subirà, M.; Alonso, P.; Segalàs, C.; Labad, J.; Orfila, C.; López-Solà, C.; Martínez-Zalacaín, I.; Via, E.; Cardoner, N.; Jiménez-Murcia, S.; Soriano-Mas, C.; et al.
Abstract: Objectives There is growing evidence supporting a role for stressful life events (SLEs) at obsessive–compulsive disorder (OCD) onset, but neurobiological correlates of such effect are not known. We evaluated regional grey matter (GM) changes associated with the presence/absence of SLEs at OCD onset.Methods One hundred and twenty-four OCD patients and 112 healthy controls were recruited. Patients were split into two groups according to the presence ( n = 56) or absence ( n = 68) of SLEs at disorder's onset. A structural magnetic resonance image was acquired for each participant and pre-processed with Statistical Parametric Mapping software (SPM8) to obtain a volume-modulated GM map. Between-group differences in sociodemographic, clinical and whole-brain regional GM volumes were assessed.Results SLEs were associated with female sex, later age at disorder's onset, more contamination/cleaning and less hoarding symptoms. In comparison with controls, patients without SLEs showed GM volume increases in bilateral dorsal putamen and the central tegmental tract of the brainstem. By contrast, patients with SLEs showed specific GM volume increases in the right anterior cerebellum.Conclusions Our findings support the idea that neuroanatomical alterations of OCD patients partially depend on the presence of SLEs at disorder's onset.